Digital Marketing Communication Strategy for Micro, Small and Medium Enterprises (MSMEs) in Business Competition - N R Rusdana; S J Choirani; A S Friska (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to analyse the marketing communication strategies carried out by micro, small and medium enterprises in the face of competition in the digital era. This study used qualitative research methods. MSMEs usually produce on a small scale and require attention in marketing the products they produce. In revolution 4.0, communication is increasingly sophisticated because it can use social media in developing a business. Marketing communication can be a strategy for every MSME to learn to introduce the products produced to other parties, so that they have the same understanding and purpose for the products and brands being sold. Various types of marketing communication mix can be selected and adapted to the types of competitive products; they must also be able to market what they produce. In the early stages, every MSME must be able to read market needs, so that they can produce products that have high competitiveness. Increasing the competitiveness of MSMEs as the spearhead of the Indonesian economy towards the global market, therefore a good marketing communication strategy is needed. By using good marketing communication, it will have an impact on the progress of the business carried out and MSMEs will grow into MSMEs that have good competitiveness.